Investment Decision Behavior Retirement Planning: An Analysis of Overconfidence Bias by Gender - Tanuatmodjo, Heraeni; Heryana, Toni; Nugraha, N; Disman, D (Jurnal ASET (Akuntansi Riset), 2024)
The purpose of the study is to determine the effect of gender moderation which is moderated again by employee status (PNS and Non PNS Lecturers) on overconfidence bias in retirement planning.  This research is included in the type of cross sectional research and the method used is the explanatory method.  The research findings are gender and employee status (civil servant and non-civil servant lecturers) moderate the effect of overconfidence bias on retirement planning. If employee status is seen based on gender, the results do not affect retirement planning. Thus in making retirement planning, employee status affects retirement planning but is not determined by gender.  This overconfidence is often stronger based on gender and employment status. In practical terms, this means that retirement planning and investment decisions are influenced by gender, as men and women have different levels of confidence. This study places the status of lecturers based on gender in moderating overconfidence bias towards retirement planning as a novelty in this study.